O aprendizado do ofício das armas: o sistema de promoção por cadetes, 1757-1897 - Adler Homero Fonseca de Castro (Navigator)
The professional formation of the officer corps is a problem that became noteworthy in the Modern Age (1492-1789). However, the academic professional education hadn’t become standard, the means for a person to acquire the necessary knowledge for a profession being the apprenticeship, the practice of an occupation. It was customary people to report for military service, as soldiers, to learn to be officers. This, together a rigid class stratification in the period, created a privileged elite of noble-apprentices, the cadets, characteristic of the unequal society of that time. In Portugal, this practice began in 1756 and in Brazil it survived into the Republic (1889), being a system of fundamental importance in the composition of the officer corps, the present text trying to present the characteristics of this type of professional education, based in social discrimination.